Meningkatkan Hasil Belajar PAK: Materi Peran Keluarga Bagi Perkembanganku dengan Model Problem Based Learning pada Kelas VII SMP Negeri 3 Matan Hilir Utara - Maria Veronika (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve students' learning outcomes in the subject of Catholic Religious Education (PAK) on the topic of "The Role of Family in My Development" for seventh-grade students at SMP Negeri 3 Matan Hilir Utara by using the Problem-Based Learning (PBL) model. The PBL model is implemented to enhance student engagement in the learning process by introducing real-life problems relevant to students' daily lives, particularly concerning the family's role in personal and moral development. The results of the study indicate that the application of the PBL model can improve students' understanding, critical thinking skills, and learning motivation. This is demonstrated by the increase in students' learning outcomes and their active participation in the learning process. PBL is effective as an innovative learning method that is relevant to students' social and emotional contexts, especially in understanding the role of the family.